2017
DOI: 10.1016/j.jalz.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Age of onset of hypertension and risk of dementia in the oldest‐old: The 90+ Study

Abstract: Introduction We investigated the association between age of onset of hypertension and dementia risk in an oldest-old cohort. Methods Participants are from The 90+ Study, a population-based longitudinal study of people aged 90+ who are survivors from the Leisure World Cohort Study (LWCS). We estimated hypertension onset age using self-reported information from The 90+ Study and LWCS, collected about 20 years earlier. 559 participants without dementia were followed every 6 months for up to 10 years. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
122
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(134 citation statements)
references
References 40 publications
(26 reference statements)
7
122
1
4
Order By: Relevance
“…Similar to data on the link between obesity and cognitive decline/dementia, studies demonstrate that later-life hypertension may be protective against cognitive decline [50,51].…”
Section: Mid-life Hypertensionsupporting
confidence: 61%
“…Similar to data on the link between obesity and cognitive decline/dementia, studies demonstrate that later-life hypertension may be protective against cognitive decline [50,51].…”
Section: Mid-life Hypertensionsupporting
confidence: 61%
“…Whereas most studies have found cardiovascular disease to be a risk factor for dementia [31, 32], our finding may be the result of survival bias, in that individuals with cardiovascular disease have increased mortality or they may develop dementia at earlier ages, which would have excluded them from the current sample. Furthermore, Corrada et al[33] found that late-life onset of hypertension was associated with reduced risk of dementia in The 90+ Study, highlighting that findings of dementia risk in the young-old may not be directly applicable to the oldest-old.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…This dovetails well with evidence that midlife risk factors lead to a late-life phenotypes. Midlife-onset hypertension is a risk factor for AD in late life; late life-onset hypertension appears to be protective of cognition 4 . What sorts of interventions might these be?…”
Section: Can We Pinpoint How Early Is “Early Enough”?mentioning
confidence: 99%